2016
DOI: 10.5334/jbr-btr.1206
|View full text |Cite
|
Sign up to set email alerts
|

Common Mistakes and Pitfalls in Magnetic Resonance Imaging of the Knee

Abstract: This pictorial review presents an overview of common interpretation errors and pitfalls in magnetic resonance imaging (MRI) of the knee. Instead of being exhaustive, we will emphasize those pitfalls that are most commonly encountered by young residents or less experienced radiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Consistent with the fact that most secondary BCs are connected to the knee joint space, [1–5] some previous studies have suggested that BCs are associated with lesions within the knee joint. [6,13–16] Balik et al retrospectively examined 45 knee MRIs of symptomatic patients.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with the fact that most secondary BCs are connected to the knee joint space, [1–5] some previous studies have suggested that BCs are associated with lesions within the knee joint. [6,13–16] Balik et al retrospectively examined 45 knee MRIs of symptomatic patients.…”
Section: Discussionsupporting
confidence: 67%
“…[1,2] Most of the BCs are secondary BCs connected with knee joint space. [1][2][3][4][5][6] BCs sometimes cause clinical symptoms such as pain or swelling. When the size become large, BC can cause knee stiffness or decrease flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Carotti et al [46] proposed the identification of early osteoarthrosis which is not based on the cartilage status, but on visible bone marrow lesions and infrapatellar fat pad synovitis. Such an approach can be explained by the so-called satisfaction of the search [47] when the detection of abnormality can reduce the detectability of other intraarticular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Complex tears in the anterior horn of the lateral meniscus were seen at arthroscopy as degeneration (Figures 1a and 1b). On sagittal images, a linear band of lateral meniscus and anterior transverse ligament, occasionally simulate an oblique meniscal tear (Figure 1b) [21][22][23]. We may have exaggerated the degeneration of meniscus as a tear due to the transverse ligament.…”
Section: Discussionmentioning
confidence: 99%